Comparative literary theory: A cross-cultural approach to English literature - Kholodniak , Olena (Research Journal in Advanced Humanities, 2023)
The comparative analysis of the known and the unfamiliar, the self and the other, forms an integral part of cultural exploration throughout history. Culture itself becomes the subject of comparison, and each act of comparison contributes to the broader understanding of cultural phenomena. The historical development of human society lacks examples of completely isolated social, cultural, and literary advancements, as interaction between various segments has always played a significant role. The degree of cultural sophistication within a society often corresponds to the intensity of its connections and exchanges with other communities. This article aims to accentuate the benefits of comparative literary theory in examining English literature from a cross-cultural standpoint and its potential impact in fostering a greater appreciation for cultural diversity. Explore literary traditions, genres, and historical contexts, emphasizing common themes and distinctive features. Engaging with the literary traditions worldwide broadens our perspectives and challenges existing notions while re-evaluating canonical texts. We emphasize the critical examination of cross-cultural influences and the transformative power of translations in interpreting and analyzing literary texts. Translations play a determining role in disseminating literary works across language barriers, allowing readers to explore different cultures through literature. We study how English literature has cross-fertilized with other literary traditions, demonstrating how a comparative approach can illuminate shared themes, motifs, and narrative techniques across different cultural contexts. Comparative literary theory helps us understand how societies influence and change their literary canons over time. A cross-cultural approach uncovers interrelatedness between different literary traditions and broadens our global perspective of English literature.